Fontes de erro em medidas eletrogoniométricas de movimentos do joelho - Sato, Tatiana de Oliveira (Universidade Federal de São Carlos, 2008)
Flexible goniometers are useful for direct movement measurements. However issues related to subject-sensor interface can introduce measurement errors. Crosstalk, i.e. the phenomenon that flexion/extension angles affect the varus/valgus angles, and vice versa, is considered as the main drawback of goniometers. It is not well known the effect of the variation between identical sensors and the crosstalk due to endblocks misalignment in frontal and transverse planes. Thus, the objective of this study was to evaluate the effect of these sources of variation to goniometer recordings. A precision jig, for simulating pure flexion/extension angles, was constructed. Goniometer sensors were attached to this jig. In the initial study six biaxial goniometers were evaluated. Each sensor showed a consistent and specific crosstalk pattern. A procedure for correction for the inherent crosstalk, based on polynomial adjust, was proposed and evaluated. This procedure provided a major reduction of the inherent crosstalk. A second study was developed to evaluate the effect of endblocks misalignments. Results showed that varus/valgus misalignments did not cause additional errors for the recordings. Rotation between endblocks was the main source of error. Compensation procedures developed in the first study were applied in this second one, also resulting in crosstalk reduction. These compensations might be required in functional movement recordings to elucidate the crosstalk effect in knee measurements and the impact of the compensation procedures in measures, such as peaks, ranges of motion and movements curves.
Keywords: Movimento; Articulação do joelho; Eletrogoniometro; Confiabilidade e Validade; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL